2014
DOI: 10.3748/wjg.v20.i47.18001
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of gemcitabine-based chemotherapies in biliary tract cancer: A meta-analysis

Abstract: AIM:To investigate the efficacy and safety of gemcitabine (Gem)-based combination chemotherapies for the treatment of advanced biliary tract cancer. METHODS:Clinical trials were identified by searching scientific literature databases (PubMed, EMBASE and the Cochrane Library) for studies published between 1975 and 2013. Two reviewers independently evaluated the relevant studies and manually searched references from these reports to locate additional eligible studies. The disease response and control rates, prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Eckel F. presented a pooled analysis of 104 trials containing 2810 evaluable patients with advanced BTCs and showed that the response rates and tumour control rates were higher for the patient subgroup receiving a combination of gemcitabine and platinum-based agents 30 . Tian-Tian Sun and Heng Liu performed a meta-analysis and systematic review in 2013 and 2014 31 , 32 and reported the efficacy and safety of gemcitabine and platinum-based chemotherapy compared with gemcitabine alone. However, many clinical trials have conflicting outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Eckel F. presented a pooled analysis of 104 trials containing 2810 evaluable patients with advanced BTCs and showed that the response rates and tumour control rates were higher for the patient subgroup receiving a combination of gemcitabine and platinum-based agents 30 . Tian-Tian Sun and Heng Liu performed a meta-analysis and systematic review in 2013 and 2014 31 , 32 and reported the efficacy and safety of gemcitabine and platinum-based chemotherapy compared with gemcitabine alone. However, many clinical trials have conflicting outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…By virtue of its distinctive features of cellular pharmacology, metabolic properties, and mechanistic characteristics, gemcitabine occupies an important place at the forefront of chemotherapy for the treatment of a wide variety of tumors (Ciccolini, Serdjebi, Peters, & Giovannetti, 2016;Crin o & Cappuzzo, 2002;Dubey, Saneja, Gupta, & Gupta, 2016;Ducoulombier, Cousin, Kotecki, & Penel, 2016;Hansen, 2001;Liu, Zhang, Li, Zhang, & Lu, 2014;Ottaiano et al, 2017;Rizzuto, Ghazaly, & Peters, 2017;Schlack, Boegemann, Steinestel, Schrader, & Krabbe, 2016;Thigpen, 2002;Zhang et al, 2017;Zhao, Guo, Sun, Lv, & Qiu, 2017). The source of cytotoxic activity of gemcitabine is primarily attributed to its ability to transport across the cell membrane to get phosphorylated efficiently, slower rate of elimination along with selfpotentiation mechanisms to mask DNA chain termination and extensive inhibitory efficiency against several enzymes (Barton- Burke, 1999;Plunkett et al, 1995;Plunkett, Huang, Searcy, & Gandhi, 1996;Plunkett, Huang, & Gandhi, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Two literatures reported the efficacy and safety comparison of gemcitabine-based combination chemotherapy and gemcitabine monotherapy [22,24] (Table 2). Lawrence Chen's meta-analysis showed [22] that combination chemotherapy was superior to single drug chemotherapy in terms of OS(WMD=-3.52,95%CI -5.14-1.35; HR = 0.65, 95% CI 0.53-0.79),PFS(WMD = 2.60, 95% CI 3.81-1.40; HR=0.63,95%CI 0.52-0.76) and ORR(OR=0.53,95%CI 0.31-0.88).…”
Section: Gemcitabine-based Chemotherapy Vsgemcitabine Monotherapymentioning
confidence: 99%
“…Lawrence Chen's meta-analysis showed [22] that combination chemotherapy was superior to single drug chemotherapy in terms of OS(WMD=-3.52,95%CI -5.14-1.35; HR = 0.65, 95% CI 0.53-0.79),PFS(WMD = 2.60, 95% CI 3.81-1.40; HR=0.63,95%CI 0.52-0.76) and ORR(OR=0.53,95%CI 0.31-0.88). In addition, among the toxic reactions reported [24] , lymphocytopenia (OR=1.82,95%CI 1.13-2.94), anemia (OR=1.96,95%CI 1.07-3.62) and neutropenia(OR=1.78,95%CI 1.19-2.66) were higher in the combined chemotherapy group than in the single chemotherapy group, while thrombocytopenia (OR=1.13,95%CI 0.60-2.14) and increased ALT levels (OR=0.76,95%CI 0.47-1.25) were not different between groups.…”
Section: Gemcitabine-based Chemotherapy Vsgemcitabine Monotherapymentioning
confidence: 99%